2020
DOI: 10.21608/svuijas.2020.68313
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some pesticides against the tomato borer, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) under laboratory conditions

Abstract: The tomato borer, Tuta absoluta (Meyrick) is considered a devastating pest, particularly to the tomato Lycopersicon esculentum. The present study was carried out to determine the efficacy of five pesticides namely, indoxacarb, (abamectin+ thiamethoxam), emamectin benzoate, fipronil and imidacloprid against the 3rd larval instar of T. absoluta under laboratory conditions using the Leaf-dip method. The tested pesticides could be descendingly arranged as follows: emamectin benzoate, fipronil, (abamectin + thiamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
2
0
0
Order By: Relevance
“…At 12.0% dose level all plant extracts showed the highest repellency rate and were in repellency F. vulgare. This support previous finding on the other research projects (Mohanny et al, 2020;Ahmed et al, 2020;Ali et al, 2019;Aly et al, 2019). Also , Pierattini et al (2019) evaluated the effect of hexane of essential oil of Pistacia lentiscus, Ocimum basilicum and Foeniculum vulgare against Sitophilus granarius.…”
Section: Discussionsupporting
confidence: 92%
“…At 12.0% dose level all plant extracts showed the highest repellency rate and were in repellency F. vulgare. This support previous finding on the other research projects (Mohanny et al, 2020;Ahmed et al, 2020;Ali et al, 2019;Aly et al, 2019). Also , Pierattini et al (2019) evaluated the effect of hexane of essential oil of Pistacia lentiscus, Ocimum basilicum and Foeniculum vulgare against Sitophilus granarius.…”
Section: Discussionsupporting
confidence: 92%
“…We conclude that the biocides used in this study had a highly significant impact on the percentage of mortality of the third instar larvae of the TLM, and thus its effect will be reflected on the population density of the pest in the future, and that the effect of these biocides increases with the increase in concentration and reading after treatment, and Spinosad showed high efficiency compared to other biocides. This agrees with what [28] found in evaluating the effectiveness of spinosad against the larval instars of TLM under laboratory conditions, it was effective and caused mortality of a large proportion of the larvae after 24 hours of treatment and the mean percentage of mortality increased gradually with the days after treatment. Laboratory study of [29] in Bulgaria showed that the biocides Azadirachtin, spinosad and B. thuringiensis var.…”
Section: Toxicity Of Biocides On Third Instar Larvae Of T Absoluta M ...supporting
confidence: 91%